Manajemen Pendidikan Karakter Melalui Muatan Lokal Keagamaan - Aliya Khamami (Pusat riset dan Inovasi Nasional, 2023)
The era of globalization is slowly eroding the characters of young people. For this reason, character education is needed. A management is needed so that good and structured character education can occur. This research method uses a qualitative descriptive method. The object of research is the students and alumni of MA NU I'anatuth-Thullab Mutih Kulon to explain the benefits of planting character education with local religious content. Local content that is applied is by studying books so that it is useful as a provision for children's knowledge about religious teachings. In addition, in establishing relationships with parents, teachers, and friends, they can behave with morality. The author hopes that this article can be used as a source of information or reference for all of us so that we can properly implement character education by balancing religion